Data on the relationship between lamotrigine and levetiracetam serum/plasma levels and toxicity: Experience at an academic medical center - Kelly E. Wood (Elsevier, 2021)
Lamotrigine and levetiracetam are second-generation anti-epileptic drugs used for the management of seizure disorders and some other medical conditions. In the related research article using retrospective data from an academic medical center, we analyzed 5046 samples originating from 1930 unique patients that had lamotrigine drug levels performed on serum/plasma and 4359 samples from 2451 patients that had levetiracetam drug levels performed. The data in this article provides the patient demographic, clinical location at time of drug level, and specific lamotrigine or levetiracetam serum/plasma drug level for all patients. For those instances with lamotrigine drug level greater than 14.0 mg/L or levetiracetam drug level of 80 mg/L or higher, additional data from chart review includes: indication for ordering the drug level, two main presenting signs or symptoms at time of drug level, timing of drug level (random, trough, peak, or unknown), changes in drug dosing following the drug level, concomitant therapy with valproic acid (lamotrigine only), and details related to drug overdose (if applicable). The analyzed data is provided in the supplementary tables included in this article. Volumes of test ordering by year is included in a figure. The dataset reported is related to the research article entitled “Correlation of Elevated Lamotrigine and Levetiracetam Serum/Plasma Levels with Toxicity: A Long-Term Retrospective Review at an Academic Medical Center” [K. E. Wood, K. L. Palmer, M.D. Krasowski, Correlation of elevated lamotrigine and levetiracetam serum/plasma levels with toxicity: A long-term retrospective review at an academic medical center, Toxicol. Rep. (2021) 8:1592-1598]